Patterns of genetic variation in Southern Hemisphere blue whales and the use of assignment test to detect mixing on the feeding grounds - LeDuc, R. G.; Dizon, A. E.; Goto, M.; Pastene, L. A.; Kato, H.; Nishiwaki, S.; LeDuc, C. A.; Brownell, R. L. (J. Cetacean Res. Manage., 2023)
A total of 111 samples from Southern Hemisphere blue whales were sequenced for 420 base pairs of the mitochondrial control region and all but one of those were genotyped over seven microsatellite loci. Comparisons were made between samples from three broad geographic regions: the southeast Pacific Ocean; Indian Ocean; and around the Antarctic continent. Each of these strata was found to be highly differentiated from the others, in both mitochondrial and nuclear data. The genetic differentiation between the geographic ranges of the nominal subspecies (i.e. true blue whales in Antarctica vs. pygmy blues in Pacific and Indian Oceans) was not markedly greater than between the populations of pygmy blue whales. Assignment tests using the microsatellite data provide some insight into detection of feeding-season mixing, although existing methods have some limitations.